2018
DOI: 10.1055/s-0038-1666868
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Opioid Use in Knee Surgery Patients

Abstract: A cross-sectional analysis of data derived from patients undergoing knee surgery at a single institution was conducted. The objectives of the study were to determine the demographic, diagnostic, and psychologic factors associated with opioid use; and to determine the clinical correlates of opioid use. We hypothesized that preoperative opioid use would be associated with worse patient-reported outcome (PRO) measures. The sample consisted of 383 patients undergoing knee surgery. The patients were classified as e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…PROMIS has proven to be effective in rapid evaluation of outcomes and reduce the burden of patients who complete the questionnaires due to its unique computer adaptive testing algorithm [12,28]. PROMIS have been increasingly adopted in orthopedic and spine conditions to capture patient-centered indicators of health status for use in clinical care, research, and cost-effectiveness analysis [5][6][7][8][9][10][11]. When compared to traditional surveys, PROMIS provides a more e cient and accurate way reporting patient symptoms, function, and healthrelated quality of life [5,6,12].…”
Section: Discussionmentioning
confidence: 99%
“…PROMIS has proven to be effective in rapid evaluation of outcomes and reduce the burden of patients who complete the questionnaires due to its unique computer adaptive testing algorithm [12,28]. PROMIS have been increasingly adopted in orthopedic and spine conditions to capture patient-centered indicators of health status for use in clinical care, research, and cost-effectiveness analysis [5][6][7][8][9][10][11]. When compared to traditional surveys, PROMIS provides a more e cient and accurate way reporting patient symptoms, function, and healthrelated quality of life [5,6,12].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies in different surgical populations have found important preoperative predictors of postoperative pain to include female gender, severity of preoperative pain, younger age, preoperative anxiety, and preoperative opioid use. 17,[50][51][52][53] The PI score was significantly associated with two procedures: (1) anterior cruciate ligament reconstruction and (2) total knee arthroplasty. Anterior cruciate ligament reconstruction is typically performed after most of the pain from the injury has subsided; consequently, it is not an unusual finding that these patients had a better preoperative PI score.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, we analysed both pre-operative opioid use and marijuana use as binary categorical variables: BYES-opioid-use^or BNO-opioid-use^, and BYES-non prescriptions drug use -marijuana^or BNO-prescription drug use -marijuana^. We have found that pre-operative opioid use is an important factor in this patient population [3], and we controlled for this in our multivariable analysis. Accurate quantification of preoperative opioid use is very difficult in orthopaedic patients as many prescriptions are provided prior to evaluation by the orthopaedic surgeon.…”
Section: Dear Editormentioning
confidence: 99%